Addendum to Draft Regulatory Analysis Proposed HEW Day Care Requirements - Department of Health, Education, and Welfare, Washington, DC. Office of the Assistant Secretary for Planning and Evaluation; Department of Health, Education, and Welfare, Washington, DC. Office of the Assistant Secretary for Planning and Evaluation ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1980)
This document is a revised and updated analysis of DHEW's draft Regulatory Analysis of June, 1979, concerning day care requirements. It estimates the impacts of changes to both the Notice of Proposed Rule Making (NPRM) proposals and the final rule -- particularly in relation to the differential impacts on center cost and supply of the group composition requirements, by geographic area, type of center, and age of children. Presented in an addendum are revisions which, taken together with the draft document, constitute the final Regulatory Analysis regarding day care requirements. The document covers eight topics: the purpose and scope of the final analysis, summary of the final rule, highlights of findings, analysis of provider requirements, analysis of state agency requirements, federal enforcement of the regulations, phasing and implementation of the regulations, and sources of data. (Author/DB)
ERIC Note: For related document, see ED 179 302.
Educational level discussed: Early Childhood Education.
Educational level discussed: Preschool Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Cost Effectiveness; Cost Estimates; Day Care; Day Care Centers; Early Childhood Education; Federal Regulation; Federal State Relationship; Health; Parent Participation; Preschool Education; School Safety; Training; DHEW Day Care Requirements; Reports, Research